Beyond Essay Structure: Competence and Literacy - Mister Gidion Maru; Ekawati Marhenny Dukut; Nihta Liando (Celt: A Journal of Culture, English Language Teaching & Literature, 2018)
This paper intends to share the making of the students’ competence and literacy awareness in the teaching of essay writing using jeremiad approach, which is so-called T-Ex, approach in EFL class. The approach suggests three aspects namely text explanation which prescribes the identification and presentation of a certain challenging issue. It is followed by the step of text examination that underlines the presence of possible solution toward the issue by referring to related knowledge and technology, socio-cultural values, and outstanding figures. It is concluded by the text expectation that proposes the hope of recalling the acquired knowledge and sharing it for future anticipation. All of the steps rely upon the language competence since they use language as a media of constructing and recognizing as well as negotiating the message(s). As a qualitative research, this study involves students as the respondents to be interviewed. Students’ Intellectual diaries and essay drafts were also regarded as data. The students were assigned to write an essay on the topic of corruption. The data are interpreted in the way of the grounded theory. The results imply that the students are encouraged and driven to search for relevant knowledge, to recall related values and figures, and to construct the future awareness. These aspects summarize the potential of combining the language competence and literacy in the classroom activities.